Trinidad, W.I. - (:unkn) unknown (A Mike Roberts Color Production, Berkeley, California; Distributed by M.Jolly, St.Augustine, Trinidad., 2009)
Description on the postcard: “Trinidad,,W.I. The steel bands like the calypso singing of Trinidad are world famous. The instruments fashioned from tops of steel drums and other discarded pieces are capable of rendering fine music under the skilful fingers of local players.”
Colour: Coloured;Style:Landscape;Other:Unbordered,Divided
Keywords: Postcards; Trinidad and Tobago; Local term--Steel Bands; Steel drum (Musical instrument); Music; Musical instrument